Some quantitative characteristics of wild Pistachio (Pistacia atlantica subsp. mutica) in Fars province of Iran - Mohammad Reza Negahdarsaber; Ali Reza Abbasi (تحقیقات جنگل و صنوبر ایران, 2012)
The aim of the study was to identify the quantitative characteristics of wild pistachio forests of Fars province of Iran and their natural regeneration. For this reason, the cluster sampling method was applied which consisted of a 20×20 km network with nine sample plots, each of 2000 m² area with crucified pattern. The results showed that the natural regeneration was weak and the number of seedlings was 5.2/ha, the average crown cover was 171.25 m²/plot and 855 m²/ha or 8.5% of total forests area. The average of plots per cluster was 7.4 and the average of crown cover per cluster was 1256.1 m². Proportion of wild pistachio trees was 7.7%, consisting of 58.3% male individuals. Most of the stands were located in mountainous areas with steep slopes covered with rock materials or shallow soils. Application of rain-fed farming, tree cutting and over grazing were the main causes of forest degradation. Forest protection and reforestation with native shrubs including wild almond species might have positive effects on rehabilitation and improvement of wild pistachio natural regeneration.